Beta 3 Adrenergic Receptor Activation Rescues Metabolic Dysfunction in Female Estrogen Receptor Alpha-Null Mice - Clookey, Stephanie L.; Welly, Rebecca J.; Shay, Dusti; Woodford, Makenzie L.; Fritsche, Kevin L.; Rector, R. Scott; Padilla, Jaume; Lubahn, Dennis B.; Vieira-Potter, Victoria J. (Frontiers in Physiology, 2019)
Metabolic disease risk escalates following menopause. The mechanism is not fully known, but likely involves reduced signaling through estrogen receptor alpha (ER), which is highly expressed in brown and white adipose tissue (BAT, WAT). Objective: Test the hypothesis that uncoupling protein (UCP1) activation mitigates metabolic dysfunction caused by loss of signaling through ER. Methods: At 8 weeks of age, female ER knock out (KO) and wild-type mice were housed at 28C and fed a Western-style high-fat, high sucrose diet (HFD) or a normal low-fat chow diet (NC) for 10 weeks. During the final two weeks, they received daily injections of CL 316,256 (CL), a selective 3 adrenergic agonist, or vehicle control (CTRL), creating 8 groups: WT-CTRL, WT-CL, KO-CTRL, KO-CL on HFD or NC; n=4-10/group. Results: ERKO demonstrated exacerbated HFD-induced adiposity gain (P<0.001) and insulin resistance (P=0.006). CL treatment improved insulin sensitivity (P<0.05) and normalized ERKO-induced adiposity increase (P<0.05). In both genotypes, CL increased resting energy expenditure (P<0.05) and induced WAT beiging indicated by increased UCP1 protein in both perigonadal (PGAT) and subcutaneous (SQAT) depots. These effects were attenuated under HFD conditions (P<0.05). In KO, CL reduced HFD energy consumption compared to CTRL (P<0.05). Remarkably, CL increased WAT ER protein levels of both WT and KO (P<0.001), revealing CL-mediated changes in estrogen signaling may have protective metabolic effects. Conclusions: CL completely restored metabolic dysfunction in ERKO mice. Thus, UCP1 may be a therapeutic target for treating metabolic dysfunction following loss of estrogen receptor signaling.